Domino 6-endo-dig Cyclization/Halogenation Reactions: Three-Component Synthesis of 1,3-Disubstituted 4-Haloimidazo[1,2-a:4,5-c′]dipyridines - Enguehard-Gueiffier, Cécile; Delaye, Pierre-Olivier; Pénichon, Mélanie; Denevault-Sabourin, Caroline; Allouchi, Hassan; Gueiffier, Alain (Synthesis, 2015)
A regiocontrolled 6-endo-dig cyclization of 3-ethynylimidazo[1,2-a]pyridine-2-carbonitriles promoted by Grignard reagent in the presence of iodine has been developed. We optimized the reaction conditions to allow the straightforward synthesis of 1,3-disubstituted 4-iodoimidazo[1,2-a:4,5-c′]dipyridines. Finally, the reactivity of the 4-iodo position toward various metal-catalyzed coupling reactions (Suzuki–Miyaura, Sonogashira, etc.) or cyanation was successfully evaluated.
Keywords: heterocycles; polycycles; cyclizations; Suzuki–Miyaura reactions; Sonogashira reactions; cyanations